Norman Rockwell : behind the camera - Schick, Ron. (New York, NY : Little, Brown and Company, 2009)
Schick explores the meticulously composed and richly detailed photographs that Rockwell used to create his famous artworks. The author delves into the archive of nearly 20,000 photographs housed at the Norman Rockwell Museum to create an intriguing work of photography, art, and Americana.
-- The illustrator and the camera / by Stephanie Haboush Plunkett -- Norman Rockwell : behind the camera -- Illustrations and features -- World War II -- Saturday Evening Post covers : the Arlington years -- Creating authenticity -- The artist as director -- Advertisements and commercial commissions -- Saturday Evening Post covers : the Stockbridge years -- Rockwell the literalist -- Look magazine.
Includes bibliographical references and index.
Keywords: Rockwell, Norman, -- 1894-1978 -- Criticism and interpretation; Painting from photographs